2022
DOI: 10.31603/bmar.v2i1.6820
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Stres Kerja, Insentif Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Mediasi

Abstract: Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh stres kerja, insentif dan lingkungan kerja terhadap kinerja karyawan dengan kepuasan kerja sebagai variabel mediasi. Alat analisis menggunakan regresi linier berganda dengan SPSS 25. Metode pengambilan sampel dengan porposive sampling dan memperoleh 52 responden. Hasil penelitian menunjukkan bahwa stres kerja dan kepuasan kerja berpengaruh negatif dan tidak signifikan terhadap kinerja karyawan. Sedangkan insentif berpengaruh positif dan tidak sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
2
3
0
2
Order By: Relevance
“…Likewise, the lower the work stress, the higher the employee's performance will be. The results of this research are in line with research conducted by Ariansy & Kurnia (2022), which states that work stress significantly negatively affects employee performance. This indicates that when employees experience work stress, employee performance decreases, so employee performance is not considered optimal.…”
Section: The Effect Of Job Stress On Employee Performancesupporting
confidence: 89%
“…Likewise, the lower the work stress, the higher the employee's performance will be. The results of this research are in line with research conducted by Ariansy & Kurnia (2022), which states that work stress significantly negatively affects employee performance. This indicates that when employees experience work stress, employee performance decreases, so employee performance is not considered optimal.…”
Section: The Effect Of Job Stress On Employee Performancesupporting
confidence: 89%
“…These results are the results of research from (Ariansy & Kurnia, 2022) that has a negative and insignificant effect on job satisfaction, so it can be concluded that the high work stress felt by employees does not affect job satisfaction. This can happen because, with stress, employees are increasingly motivated to provide all abilities and resources, so that they can meet work requirements and needs.…”
Section: The Effect Of Work Stress On Job Satisfactionsupporting
confidence: 54%
“…Oleh karena itu, setiap level struktural dan fungsional harus dimanfaatkan secara maksimal. Untuk menjaga agar perusahaan tetap bertahan dan berjalan sesuai dengan tujuan, maka harus menjaga dan meningkatkan sumber daya yang dimilikinya, termasuk meningkatkan kinerja karyawan (3). (Hani Darmawati, 2021) Kinerja merupakan perilaku nyata yang ditampilkan setiap orang sebagai prestasi kerja yang dihasilkan oleh karyawan sesuai dengan perannya (4).…”
Section: Aunclassified